How Supply Chain Regulates the Innovations Study of Diffusion in Public Service Organizations? Recommendations of Reform - Alfiyan Darojat; Dian Ekowati; Indrianawati Usman (International Journal of Supply Chain Management, 2020)
This investigation will examine the effect of innovation, innovation process and performance on public service organizations with the moderating effect of supply chain management (Information Sharing). Why is innovation important for public service organizations? Public service innovation is an important concern in bureaucratic reform efforts. The need for bureaucratic reform, especially in public services, in an effort to fulfil the right to obtain services provided by the government. This study will gather data by using questionnaires and PLS-SEM was used for analysis. This study will present a systematic framework and methodology based on the synthesis of the results of the review so that it can be used as a rationale and recommendation for public service reform and innovation in Indonesia. The results of a systematic framework and methodology can be used in the broader context of public service organizations.